Hemisection of the upper right first molar with a grade-2 furcation lesion: case report - Ristyawati, Agatha; Chrysandra, Yustika; Untara, Tri Endra; Nugraheni, Tunjung; Enggardipta, Raras Ajeng (Fakultas Kedokteran Gigi Universitas Padjadjaran, 2025)
Introduction: Hemisection is the separation procedure of multiple root teeth from the crown to the furcation and removing one damaged root with periodontium abnormalities, followed by a fixed denture treatment for retaining partially damaged posterior teeth. This case report aims to demonstrate the clinical management of a maxillary first molar with grade-2 furcation involvement using a multidisciplinary approach consisting of endodontic treatment, surgical hemisection, and prosthodontic rehabilitation, and to highlight hemisection as a conservative tooth-preserving treatment option compared with extraction and implant therapy. Case report: A female patient, 56 years old, visited the Dental Conservation Clinic of Prof. Soedomo RSGM with discomfort in the right upper molars when chewing. Based on the dental and radiograph examination, the diagnosis was pulp necrosis with asymptomatic apical periodontitis. Beginning with root canal treatment, the damaged mesial root of tooth 16 was hemisected; triangular flap was prepared in the buccal region of the maxillary right first molar; the tooth was divided mesial-distally; mesial root was removed; socket was debrided; the flap was sutured with interrupted technique and the surgical wound was closed. A modified ridge lap pontics denture design was discussed with the Prosthodontia specialist. Conclusion: A root canal-treated abutment tooth followed by hemisection was confirmed to be a better treatment choice in this case over extraction, with the goal of retaining the tooth with the damaged root in the mouth and restoring dental function.Hemiseksi gigi molar pertama kanan atas dengan lesi furkasi derajat-2: laporan kasusPendahuluan: Hemiseksi adalah prosedur pemisahan beberapa akar gigi dari mahkota sampai ke furkasi dan pencabutan satu akar yang rusak dengan kelainan periodontal, dilanjutkan dengan perawatan fixed bridge untuk mempertahankan gigi. Laporan kasus ini bertujuan untuk menunjukkan pengelolaan klinis gigi molar pertama rahang atas dengan keterlibatan furkasi derajat 2 menggunakan pendekatan multidisiplin yang meliputi perawatan endodontik, hemiseksion bedah, dan rehabilitasi prostodontik, serta menyoroti hemiseksion sebagai opsi perawatan konservatif yang mempertahankan gigi dibandingkan dengan ekstraksi dan terapi implan. Laporan kasus: Seorang pasien wanita, 56 tahun, datang ke Klinik Konservasi Gigi RSGM Prof. Soedomo dengan keluhan rasa tidak nyaman pada gigi geraham kanan atas saat mengunyah. Diagnosis berdasarkan pemeriksaan gigi dan radiografi adalah nekrosis pulpa dengan periodontitis apikal asimptomatik. Dilakukan perawatan saluran akar, hemiseksi akar mesial gigi 16 yang mengalami kerusakan dilakukan pada kunjungan berikutnya, insisi dengan triangular flap dilakukan pada daerah bukal gigi molar pertama kanan atas, gigi diseparasi mesial dan distal, akar mesial diekstraksi, debridemen soket mesial, flap dijahit dengan teknik interrupted. Desain fixed bridge berupa modified ridge lap pontics yang telah didiskusikan dengan spesialis Prostodonsia. Kesimpulan: Perawatan saluran akar gigi penyangga yang diikuti dengan hemiseksi dipastikan menjadi pilihan perawatan yang lebih baik dalam kasus ini daripada pencabutan gigi dengan tujuan mempertahankan gigi dengan salah satu akar yang rusak di dalam mulut dan mengembalikan fungsi gigi.